Estudo de radionuclídeos naturais em águas de aquíferos da região metropolitana de Belo Horizonte - Carla Pereira Ricardo (2012)
The metropolitan area of Belo Horizonte - MABH which is composed of thirty four of Minas Gerais counties, lies on a granitic-gnassic foundation that promotes the occurrence of uranium and thorium series radionuclides in underground water. In some cities in this region these waters are used for urban and rural supply. This has motivated the interest of determining the levels of natural radioactivity in the waters of the aquifers of the MABH, since the geological constitution of an aquifer contributes to the quality of water. The aim of this study was to evaluate the presence and distribution of total alpha emitters and total beta emitters, uranium (238U and 234U), thorium (232Th), radium (226Ra), and radon (222Rn) in six tube wells of different aquifers of MABH by applying a set of analytical techniques. Physical and chemical parameters were also evaluated, such as pH, oxidation-reduction potential (Eh), temperature, conductivity, resistivity, total dissolved solids, alkalinity and hardness. Using a portable meter, it was possible to determine the physical and chemical parameters of these waters and according to the results, the underground water analyzed was within the drinking patterns established by the Brazilian Ministry of Health, in relation to hardness and total dissolved solids at all points. However, the waters of Carst 1 and Carst 2 are more acidic than recommended, and the water at Point Gnaiss 2 is on the threshold. In order to achieve the determination of the concentration of radionuclides, the techniques used were: mass spectrometry, ICP-MS, alpha spectrometry, the RAD7 radon detector, and the direct count of dry residue. The dissolved uranium concentrations found ranged between 0.017 and 4.63 g·L-1, all below the Maximum Allowed Value (MAV) according to the Health Ministry Ordinance No. 2,914. and thorium concentration ranged between 0.01 and 0.099 g·L-1. The 238U concentrations varied between 4.6·10-4 and 6.1·10-2 Bq·L-1 and 234U concentrations ranged from 9.1·10-4 and 8.2·10-2 Bq·L-1 which, in accordance to the diagram of Cowart & Osmond, resulted in isotopic activity ratios (RA) of stable systems, normal reducer and normal oxidizing environments, being in just one point, the Carst 4, the environment considered behind in accumulation in formation. The concentration of radon in water varied between 6.5 and 230.0 Bq·L-1. 226Ra activity concentrations ranged from 2.0·10-2 and 6.0·10-2 Bq·L-1. The determined gross beta radioactivity concentrations ranged between 0.10 and 0.39 Bq·L-1, all below the maximum allowable value (MAV) from the Health Ministry Ordinance No. 2,914 (MAV = 1.0 Bq·L-1). However, determined gross alpha radioactivity concentrations ranged between 0.04 and 0.54 Bq·L-1. The results indicate that a broader survey of natural radioactivity should be carried out in the waters of RMBH. This proves to be feasible with the techniques used in this field work. This action is necessary because only one point studied this region showed radon activity concentration below the limit provided by in US legislation to this radioisotope, responsible for half of human exposure to radioactivity.